Essay on the Principle of Population : The 1803 Edition - Malthus, Thomas Robert; Stimson, Shannon C. (New Haven, CT : Yale University Press, 2018)
Malthus's Essay on the Principle of Population remains one of the most influential works of political economy ever written. Most widely circulated in its initial 1798 version, this is the first publication of his benchmark 1803 edition since 1989. Introduced by editor Shannon C. Stimson, this edition includes essays on the historical and political theoretical underpinnings of Malthus's work by Niall O'Flaherty, Malthus's influence on concepts of nature by Deborah Valenze, implications of his population model for political economy by Sir Anthony Wrigley, an assessment of Malthus's theory in light of modern economic ideas by Kenneth Binmore, and a discussion of the Essay's literary and cultural influence by Karen O'Brien. The result is an enlarged view of the political, social, and cultural impact of this profoundly influential work.
Frontmatter -- Contributors -- Contents -- Acknowledgments -- Introduction / Stimson, Shannon C. -- Note on the Text -- Texts. AN ESSAY ON THE PRINCIPLE OF POPULATION -- PREFACE -- Contents -- BOOK I. Of the Checks to Population in the less civilized parts of the world, and in past times -- BOOK II. Of the Checks to Population in the different States of Modern Europe -- BOOK III. Of the different Systems or Expedients which have been proposed or have prevailed in Society, as they affect the Evils arising from the Principle of Population -- BOOK IV. Of our future Prospects respecting the removal or mitigation of the Evils arising from the Principle of Population. -- Essays -- Malthus and the History of Population / O'Flaherty, Niall -- The Tortoise and the Hare / Valenze, Deborah -- The Preventive Check and the Poor Law / Wrigley, E. A. -- Malthusian Economics / Binmore, Kenneth -- The Cultural and Literary Significance of the 1803 Essay / O'Brie, Karen -- Bibliography -- Index
Mode of access: Internet via World Wide Web.
In English.
Description based on online resource; title from PDF title page (publisher's Web site, viewed 22. Okt 2019)
Keywords: Population; BUSINESS & ECONOMICS / Economics / Theory